In silico functional and structural characterization of hepatitis B virus PreS/S-gene in Iranian patients infected with chronic hepatitis B virus genotype D. Issue 7 (July 2020) - Khodadad, Nastaran; Seyedian, Seyed Saeed; Moattari, Afagh; Biparva Haghighi, Somayeh; Pirmoradi, Roya; Abbasi, Samaneh; Makvandi, Manoochehr
Abstract: Objective: Chronic hepatitis B (CHB) virus infection is the most prevalent chronic liver disease and has become a serious threat to human health. In this study, we attempted to specify and predict several properties including physicochemical, mutation sites, B-cell epitopes, phosphorylation sites, N-link, O-link glycosylation sites, and protein structures of S protein isolated from Ahvaz. Materials and methods: Initially, hepatitis B virus DNA ( HBV DNA) was extracted from five sera samples of untreated chronic hepatitis B patients. The full-length HBV genomes were amplified and then cloned in pTZ57 R/T vector. The full sequences of HBV were registered in the GenBank with accessions numbers (MK355500), (MK355501) and (MK693107-9). PROTSCALE, Expasy's ProtParam, immuneepitope, ABCpred, BcePred, Bepipred, Algpred, VaxiJen, SCRATCH, DiANNA, plus a number of online analytical processing tools were used to analyse and predict the preS/S gene of genotype D sequences. The present study is the first analytical research on samples obtained from Ahvaz. Results: We found major hydrophilic region (MHR) mutations at "a" determining region that included K122R, N131T, F134Y, P142L, and T126N mutations. Moreover, Ahvaz sequences revealed four sites (4, 112, 166, and 309) in the preS/S gene for N-glycosylation that could possibly be a potential target for anti- HBV therapy. Conclusion: In the present study, mutations were identified at positions T113S and N131T within the MHR region of S protein; these mutations can potentially decrease the effect of hepatitis B vaccination in vaccine recipients. Abstract : Bioinformatics; Immunology; Microbiology; Genetics; Molecular biology; In silico; Chronic hepatitis B; Mutations; Iran.